Desmoplastic Fibroma of the Pediatric Cranium: An Aggressive Skull Tumor with Local Recurrence - KOISO, Takao (Neurol Med Chir (Tokyo), 2016)
Cranial desmoplastic fibroma (DF) is extremely rare and only 20 cases, including only 7 pediatric cases, have been reported previously. We describe the first case of a child with cranial DF that increased in size over a short-term and recurred after resection. The aim of this case report was to discuss the clinical, radiological, and histological characteristics and optimal treatment for this rare and aggressive skull tumor.